Baiting the Nine-banded Armadillo - Holly K. Ober; Lucas W. DeGroote; Russell F. Mizell (EDIS)
What is the tastiest treat to tempt an armadillo? Armadillos are one of the most significant nuisance pests in Florida and much of the Southeast. There are no repellents, toxicants, or fumigants registered for use with them. They are good at both burrowing beneath and climbing over fences. There are also no effective methods for baiting them into traps. So, the authors of this 3-page fact sheet set up a test to determine which materials have the greatest potential to serve as bait. Written by Holly K. Ober, Lucas W. DeGroote, and Russell F. Mizell III, and published by the UF Department of Wildlife Ecology and Conservation, December 2011. Reviewed October 2014.